Insect Conservation Biology: Proceedings of the Royal Entomological Society’s (23rd Symposium) - Stewart, A.J.A (CABI, 2014)
Insects present conservationists with a very different set of challenges in comparison with more popular groups such as vertebrate animals and vascular plants. These are a consequence of several aspects of their life histories that make them especially vulnerable to the types of environmental changes currently being experienced across many temperate regions (McLean, 1990; Kirby, 1992; UK Biodiversity Group, 1999). Many insects have highly specialized habitat (and often microhabitat) requirements that are further complicated by the fact that the discrete stages in the life cycle often require radically different resources. Most insects have comparatively short life cycles (often annual or more frequent) with no dormant stage in which they can escape adverse conditions, so that these habitat requirements have to be met without interruption. Finally, many species are incapable of dispersing more than trivial distances, or are behaviourally reluctant to do so, resulting in their complex habitat requirements having to be met within relatively small areas and an increased sensitivity to habitat fragmentation. Thus, maintenance of habitat quality, continuity, heterogeneity and connectedness are recurrent themes in insect conservation biology.